Computational structural mechanics : static and dynamic behaviors. - Pradhan, Karan Kumar; Chakraverty, Snehashish (London : Academic Press an imprint of Elsevier, 2019)
Computational Structural Mechanics: Static and Dynamic Behaviors provides a cutting-edge treatment of functionally graded materials and the computational methods and solutions of FG static and vibration problems of plates. Using the Rayleigh-Ritz method, static and dynamic problems related to behavior of FG rectangular, Levy, elliptic, skew and annular plates are discussed in detail. A thorough review of the latest research results, computational methods and applications of FG technology make this an essential resource for researchers in academia and industry.
Includes bibliography and index.
Keywords: Structural analysis (Engineering) -- Mathematics; Engineering mathematics